Dedifferentiation and redifferentiation of canine articular chondrocytes - Penny, Jasmine Rachel (2015)
Articular cartilage can be damaged directly through injury or osteoarthritis (OA). This tissue is very poor at regenerating itself due to its avascular nature and the immobility of chondrocytes within the tissue. There are a range of surgical techniques to repair cartilage lesions. Cellular therapies such Autologous Chondrocyte Implantation (ACI) and later modifications have been used to repair cartilage lesions for the past two decades. However, there is currently no completely successful treatment of cartilage lesions, with the newly generated cartilage often possessing very poor mechanical properties. Also, cell-based therapies require large numbers of chondrocytes which have to be expanded in monolayer. A consequence of this expansion is a loss of the chondrocyte phenotype (dedifferentiation). The overall aim of this thesis was to develop a greater understanding of chondrocyte dedifferentiation and redifferentiation in vitro using canine chondrocytes. Dogs can also suffer with OA and have been used extensively as a model for OA. Firstly, canine chondrocytes were expanded in monolayer up to P5 to confirm dedifferentiation. These cells were shown to have lost their typical chondrocytic phenotype through decreased expression of collagen type II and increased expression of collagen type I and CD44. A considerable part of this element of the thesis also involved identifying antibodies that would cross-react with the target canine antigens. The next aim of the thesis was to redifferentiate dedifferentiated chondrocytes through three-dimensional (3D) culture. Initial problems with high density pellet culture led to the selection of a supporting material. Alginate was chosen as it is a naturally occurring polymer which has previously been used to culture chondrocytes in 3D. After making several adjustments to the set-up and downstream analysis of the beads, chondrocytes from different passages were seeded into them. Alginate beads seeded with P2 chondrocytes appeared to contain cells with a more chondrocyte-like phenotype compared to P3- and P4-seeded beads. However, expression of collagen type I was still relatively high in P2-seeded beads, indicating 3D culture alone is not enough to induce complete redifferentiation. Therefore, the final aim of this thesis was to enhance the redifferentiation of dedifferentiated canine chondrocytes. Two initial conditions were selected; addition of 25μg/ml ascorbate to the culture medium and incubating the beads under reduced oxygen conditions (2.4%). Culturing the beads under reduced oxygen conditions (2.4%) appeared to enhance redifferentiation. However addition of ascorbate to the culture medium had mixed results. This culture system can now be further adapted and modified to better enhance chondrocyte redifferentiation. This work could include combining the two conditions already tested as well as adding growth factors to the culture medium. More successful maintenance of the chondrocyte phenotype in vitro, could potentially lead to better articular cartilage regeneration both in vitro and in vivo.